2021
DOI: 10.1111/jgh.15642
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and polyp detection in colonoscopy: Use of a single neural network to achieve rapid polyp localization for clinical use

Abstract: Background and Aim Artificial intelligence has been extensively studied to assist clinicians in polyp detection, but such systems usually require expansive processing power, making them prohibitively expensive and hindering wide adaption. The current study used a fast object detection algorithm, known as the YOLOv3 algorithm, to achieve real‐time polyp detection on a laptop. In addition, we evaluated and classified the causes of false detections to further improve accuracy. Methods The YOLOv3 algorithm was tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It could accomplish an excellent effect in a short time. It was economical and affordable, making it suited for large-scale promotions in underdeveloped areas ( 88 ). Some adenomas and polyps detected by the real-time CADe system are small and low risk.…”
Section: The Application Of Ai In Crc Diagnosismentioning
confidence: 99%
“…It could accomplish an excellent effect in a short time. It was economical and affordable, making it suited for large-scale promotions in underdeveloped areas ( 88 ). Some adenomas and polyps detected by the real-time CADe system are small and low risk.…”
Section: The Application Of Ai In Crc Diagnosismentioning
confidence: 99%
“…The software, hardware, and interface platforms are already available. A study showed that a commercially available desktop graphics processing unit can already run some of these algorithms, making it attractive for low‐middle‐income countries 28 . This may allow for technology leapfrogging if colonoscopy‐based AI‐enhanced screening programs become more mainstream.…”
Section: Potential Future Screening Strategiesmentioning
confidence: 99%
“…This could be due to being hidden behind mucosal folds or concealed by poor bowel preparation. In a study that evaluated false detections with CADe in colonoscopy, (38) blurry images were found to result in distorted polyp texture and were one of the reasons for false negative detections. These false negative detections also occurred when polyps approached the corner of a frame just before appearing or disappearing from the FOV.…”
Section: R E V I E W a R T I C L Ementioning
confidence: 99%